A phylogenetic analysis between humans and D. melanogaster: A repertoire of solute carriers in humans and flies. - Ceder, M.M.; Fredriksson, R. (Gene, 2022)
The solute carrier (SLC) superfamily is the largest group of transporters in humans, with the role to transport solutes across plasma membranes. The SLCs are currently divided into 65 families with 430 members. Here, we performed a detailed mining of the SLC superfamily and the recent annotated family of "atypical" SLCs in human and D. melanogaster using Hidden Markov Models and PSI-BLAST. Our analyses identified 381 protein sequences in D. melanogaster and of those, 55 proteins have not been previously identified in flies. In total, 11 of the 65 human SLC families were found to not be conserved in flies, while a few families are highly conserved, which perhaps reflects the families' functions and roles in cellular pathways. This study provides the first collection of all SLC sequences in D. melanogaster and can serve as a SLC database to be used for classification of SLCs in other phyla.